Funções de onda de mésons na frente de luz - Silveira, Roberto Correa da (2019)
In this thesis we study the projection of the Poincaré covariant wave function of pseudoscalar mesons on the light front, which is the parton distribution amplitude. The hadronic states we consider are flavorless and flavored light mesons with unequal quark masses. The wave function projected on the light front is obtained from numerical solutions of the Bethe-Salpeter equation for light and heavy-light mesons, whose constituents, the quarks, are described by nonperturbative solutions of the Dyson-Schwinger equation for each quark flavor. Both integral equations are truncated and related by an axialvector Ward-Takahashi identity that guarantees chiral symmetry in the limit of vanishing current quark masses. On the other hand, the nonperturbative features of the interaction kernel in these equations give rise to dynamical chiral symmetry breaking, which is at the origin of meson’s mass scale much larger than the current-quark masses. Moreover, the quark-mass asymmetry in heavy-light mesons increases its complexity due to an array of energy scales and results in the heavier quark carrying a larger fraction of the meson’s total momentum. The resulting parton distribution amplitude of the kaon is therefore asymmetric compared with the one of the pion and both are considerably wider than the asymptotic distribution on the light front. This broadening of the distribution amplitudes is a direct consequence of dynamical chiral symmetry breaking.